Experimental and numerical analysis on a compact liquid metal blade heat dissipator with twin stage electromagnetic pumps. (May 2019) - Wang, Yushu; Zhang, Pengju; Tan, Sicong; Yao, Siyuan; Fan, Pan; Liu, Jing; He, Zhizhu; Rao, Wei
Abstract: For cooling system, liquid metal (LM) have attracted many attentions as an excellent coolant. In this study, we propose a superior liquid metal cooling blade dissipator with twin stage electromagnetic pumps (EMPs), whose thinnest dimension was only 4 mm. The coupling model is utilized to solve the distribution of Lorentz force and the field of velocity and temperature simultaneously in the COMSOL multi-physics software, and the validity of numerical model was verified by experimental data. It is demonstrated that the efficiency of twin stage EMPs was obviously higher than that of single stage of EMP at the same input power theoretically. The Nusselt number at the heater is calculated under the different driven current and heating power. It has been found that there was no obvious change for Nusselt number. Also it can be concluded that the superior property of suppressing thermal shock and high performance-cost ratio were presented.